Down in the dungeons: the hidden role of diatom biofilms and microbial activity in the biogeochemistry of a dynamic estuarine point bar - Duteil, Thibault; Bourillot, Raphaël; Braissant, Olivier; Henry, Adrien; Franceschi, Michel; Olivier, Marie‐Joelle; Le Roy, Nathalie; Brigaud, Benjamin; Portier, Eric; Visscher, Pieter T (Sedimentology, 2025)
In many estuaries, biogeochemical investigations have often focused on transient diatom biofilms that form on low‐energy intertidal flats. Studies on microphytobenthos in high‐energy sedimentary environments are unusual. The present investigation focuses on the biogeochemistry to a depth of 6 m of a fluvio‐estuarine point bar from the Garonne channel (SW France) impacted by both tidal current and tidal wave, where three sediment cores were taken. Porewater chemistry was analysed with microelectrodes (pH, oxygen and sulfide), ion chromatography and inductively‐coupled‐plasma spectrometry (for major elements) and colorimetric assays (for iron speciation). Porewater composition was compared to measurements of microbial activity including isothermal calorimetry and metabolic assays using triphenyltetrazolium chloride and fluorescein diacetate to determine the distribution of predominant microbial metabolisms in the sediment. Finally, bulk sediment chemistry was characterized through X‐ray fluorescence core scanning. Sediments are heterolithic, made of decimetre to meter thick alternating sand and mud. The uppermost 60 cm of the point bar sediment show a mostly classical vertical succession of microbial metabolisms: (i) oxygenic photosynthesis occurs mostly in diatom biofilm forming in the uppermost millimetres; (ii) aerobic respiration between 0 cm and 1 cm, (iii) nitrate reduction between 6 cm and 16 cm, partially overlapping (iv) sulfate reduction between 10 cm and 25 cm, (v) manganese oxide reduction below 2 cm and (vi) iron oxide reduction below 16 cm. Measurements of metabolic activity, elevated in areas showing significant geochemical changes, confirmed the impact of microbial metabolism on the composition of pore water. The highest metabolic activity coincides with areas where oxygen, nitrate and sulphate concentrations are decreasing. Hydrolytic activity peaked in the zone of aerobic respiration, possibly in part due to enzymatic degradation of organic matter (e.g., extracellular polymeric substances) produced in surface diatom biofilm. Low concentrations of nitrates and sulfates were measured in sands at 1.3 to 1.6 m and 3.2 m depth, coinciding with a renewed increase in hydrolytic activity and metabolically active cells. Because of the sediment heterolithic composition and the point bar architecture made of laterally accreting layers, subsurface advection of porewater through permeable horizons could explain the local increases of nitrate and sulfate reduction. Impacts of microbial metabolism on early diagenesis were modelled using PHREEQC software and outcomes predicted the potential precipitation of metastable iron and/or sulfides. This was confirmed by X‐ray fluorescence analyses showing a coinciding increase of sulfur, Fe and/or Mn at several depths (e.g., 15 to 60 or 560 to 580 cm). Based on our observations, we propose a biogeochemical model that links microbial metabolisms and early diagenesis to the complex vertical sedimentary architecture of an estuarine point bar. Our results show that high‐energy estuarine point bars are subject to an active biogeochemical cycling of C, S, N, Fe and Mn quite similar to that of intertidal mudflat, but locally altered by the sedimentary architecture of the point bar, resulting in lateral advection of porewater.